Homophobia, transphobia, young people and the question of responsibility. Issue 1 (2nd January 2017) - Rasmussen, Mary Lou; Sanjakdar, Fida; Allen, Louisa; Quinlivan, Kathleen; Bromdal, Annette
ABSTRACT: Young people may face conflicting and confusing messages about what it means to respond well in relation to homophobia and transphobia. Consequently, we ask – What might it mean to respond well to homophobia and transphobia? This strategy, inspired by Anika Thiem and Judith Butler, is recognition of the ambivalent conditions which structure attempts to respond well to bullying related to gender and sexuality. Such an approach is counter to educational responses that suggest a remedy in advance of the enactment of perceived bullying. Our paper draws on research conducted by the authors in four such schools, two in Australia and two in Aotearoa/New Zealand. It is a deliberate turn away from focusing on who should be held to account for homophobia and transphobia.